Identificación de la potencialidad turística para el desarrollo local y emprendimientos del Cantón Bolívar Provincia de Manabí. - Sacón Sacón, Johanna Maricela (2018)
The present non-experimental research uses a cross-sectional design using the synthetic analytical method and the deductive inductive method. Its general objective is to determine the tourist potential for local development and undertakings in the Bolívar canton; a methodology resulting from the analysis of several authors is proposed, composed of three phases: in the first, a situational tourism diagnosis is made, where the basic services and tourism infrastructure are characterized, the tourism inventory is updated using the MINTUR inventory cards obtained as Results The identification of twenty-one tourism resources, the ventures are identified evaluating the tourism management through an interview that as a result showed the lack of professionals to manage tourism and the low budget allocated to the sector. The second phase consisted in a study of the tourist market, the offer was analyzed identifying fourteen lodging establishments, forty-one restaurants and twelve amusement centers; the study of the demand showed in its market segmentation a potential young tourist, who looks for fun, travels alone and sleeps for more than five days, in addition a matrix was applied to determine the direct competitor of the canton resulting to be Chone canton. And in the third and final phase, a business plan for tourism ventures is designed applying the SWOT matrix and the potentialities to determine the possible ventures and the identification of strategies aimed at the local tourist development of the territory such as: encouraging the creation of ventures, preparation of new products, tourism promotion and financing.